Measuring Mental Toughness among Students of the Kindergarten Department in the Universities of the Kurdistan Region of Iraq (Constructing and Application) (2022) - Ali Hasan , Sharmin; Ahmed Ameen, Salwa (Zanco Journal of Human Sciences, 2023)
This research aimed to the following objectives: Constructing a scale of mental toughness among the students of the kindergarten department in the universities of the Kurdistan Region of Iraq, and also aims to applying the scale of mental toughness to measure the level of mental toughness among students of the kindergarten department in the universities of the Kurdistan Region. Where the researchers used the descriptive method for its suitability to the nature of the research, and the Research Population includes the students of the kindergarten department in the universities of Kurdistan Region for the academic year (2021-2022) in the morning study. In order to achieve the objectives of the current research, the researchers built a measure of mental toughness, and for this purpose, the construction sample (statistical analysis) was selected from the original Population by 40%, as the construction sample amounted to (483) students. Where it was chosen by stratified random method, and after conducting the scale building procedures, the researchers built a scale to measure mental toughness consisting of (52) self-reporting items, distributed over (7) components, which included each of: Goal commitment: (7, items), challenge and perseverance (7, items), life control: (8, items), emotional stability (7, items), self-efficacy (8, items), positive energy (7, items), self-confidence: (8, items) , and it consists of (5) five answer alternatives, which extracted the appropriate psychometric properties of the scale items, which included: (discriminatory power, item validity, and item reliability), and the psychometric properties of the scale were extracted, which included: (face validity and constrict validity), and reliability: (The method of re-testing and the alpha-Cronbach equation), and to apply the scale in its final form, the researchers chose the applied sample from the original Population at a rate of (20%), as its number was (242) students, which were chosen by the stratified random method, by depending on Statistical Package of Social Sciences (SPSS) to analyze the data, the current research reached the most important results according to The objectives of the research included the following: The scale was constructed to measure mental toughness among the students of the kindergarten department in the universities of the Kurdistan Region of Iraq which consists of (52) self-reporting items and is characterized by proper psychometric properties, And the students of the Kindergarten Department in the universities of the Kurdistan Region of Iraq are characterized by mental toughness in general and at a high level, and in conclusion and in light of the results of the research, the researchers reached some recommendations and suggestions.